HEALTHY ME: INNOVATIVE SOLUTIONS THROUGH HEALTHY FAST-FOOD INNOVATION - Yenita, Yenita; Wijaya, Septihani Michella (Graduate Program of Universitas Tarumanagara, 2023)
Everyone wants to live healthy. In addition to a regular lifestyle, diligent exercise, of course food is also a determining factor for one's health. In the current pandemic, public awareness to eat healthy food is increasing. Eating healthy foods every day is highly recommended to meet nutritional needs and maintain immunity. Modern lifestyle makes Indonesian people prefer fast food because it is considered more practical when cooked and consumed. However, fast food is not good for health if consumed too often because it contains saturated fat and food ingredients that are harmful to the body, such as chewing agents, preservatives, and dyes. Fast food can be prepared quickly, and dishes are ready to eat as soon as they are served. Processing and preparation of these foodstuffs is easier. Many types of food that can be an option for those who are busy. There is a stigma in Indonesian society that considers fast food to be junk food, even though not all fast food is unhealthy. HEALTHY ME is here to overcome this problem by providing fast food that prioritizes consumer health, by offering a variety of healthy fast food menu options, HEALTHY ME does not use food ingredients that contain animal protein, so it is safe for consumption by most people, and most importantly HEALTHY ME uses quality ingredients and no preservatives.